Problems Of The Land Use And Food Supply In Bashkortostan - Galiev, Rustam Ravilovich (Economy of Regions, 2015)
The research is devoted to the problems of food supply of the population of the region. Subject matter of the research is the relations developed in the conditions of economic reforms in the field of agrarian land use in the Republic of Bashkortostan. Purpose of the work is to develop recommendations on improvement of a situation of the food self-sufficiency and effective land use in Bashkortostan. The research is based on the dialectic approach and economic-mathematical method of the research. The results of the research testify the need of revision of such land features as an indispensability and not susceptibility to obsolescence in the conditions of further growth and development of scientific and technical progress to prevent a lag between our country and developed foreign countries in the theory of rural economics and practice of the food supply. At the differentiation of subsidies for 1 liter of milk and on 1 head of uterine livestock of breeding cattle (on 1 cow, an ewe, a goat) as a correcting indicator, it is expedient to use the cadastral cost of the farmland as an integrated indicator reflecting fertility of arable and fodder grounds, an spareness, rockiness, a slope corner, transport availability or remoteness. Results of the research are applicable in the scientific and educational sphere, connected with the rural economics theory, and also in state bodies agriculture at the distribution of subsidies between market participants. Land is replaceable and worn-out means of production in agriculture, and also a basis for the enterprise placement. Ignoring of the remoteness of lands, the soil qualities, and technological properties leads to the state regulation of agriculture without including the nature efficiency of agrarian landscapes.